2015
DOI: 10.1002/anie.201503407
|View full text |Cite
|
Sign up to set email alerts
|

NiSe Nanowire Film Supported on Nickel Foam: An Efficient and Stable 3D Bifunctional Electrode for Full Water Splitting

Abstract: Active and stable electrocatalysts made from earth-abundant elements are key to water splitting for hydrogen production through electrolysis. The growth of NiSe nanowire film on nickel foam (NiSe/NF) in situ by hydrothermal treatment of NF using NaHSe as Se source is presented. When used as a 3D oxygen evolution electrode, the NiSe/NF exhibits high activity with an overpotential of 270 mV required to achieve 20 mA cm(-2) and strong durability in 1.0 M KOH, and the NiOOH species formed at the NiSe surface serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
901
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,315 publications
(954 citation statements)
references
References 60 publications
52
901
1
Order By: Relevance
“…Obviously the specific current density of the NiO/Ni/C sample is indeed higher than that of the ALD-NiO/C and Ni/C samples under a certain applied voltage, in which the current densities for the NiO/Ni/C samples of 10 mA·cm −2 and 100 mA·cm −2 are achieved at low overpotential vs. the reversible hydrogen electrodes (RHE) of 189 and 337 mV, respectively. The overpotential of NiO/Ni nanoparticles loaded at carbon fiber paper at 10 mA·cm −2 is smaller than most recently reported HER catalysts in alkaline solution [18,19,20,21,22,23,24,25,26], including CoNx/C (247 mV) [19], NiFe layered double hydroxide (LDH)/Ni foam (210 mV) [21], CoP/CC (209 mV) [24], and N-Co@G (337 mV) [26]. The highest HER activity of the NiO/Ni/C sample results from the NiO/Ni nanoparticles during the annealing process with reduction and mild oxidation treatment.…”
Section: Resultsmentioning
confidence: 72%
“…Obviously the specific current density of the NiO/Ni/C sample is indeed higher than that of the ALD-NiO/C and Ni/C samples under a certain applied voltage, in which the current densities for the NiO/Ni/C samples of 10 mA·cm −2 and 100 mA·cm −2 are achieved at low overpotential vs. the reversible hydrogen electrodes (RHE) of 189 and 337 mV, respectively. The overpotential of NiO/Ni nanoparticles loaded at carbon fiber paper at 10 mA·cm −2 is smaller than most recently reported HER catalysts in alkaline solution [18,19,20,21,22,23,24,25,26], including CoNx/C (247 mV) [19], NiFe layered double hydroxide (LDH)/Ni foam (210 mV) [21], CoP/CC (209 mV) [24], and N-Co@G (337 mV) [26]. The highest HER activity of the NiO/Ni/C sample results from the NiO/Ni nanoparticles during the annealing process with reduction and mild oxidation treatment.…”
Section: Resultsmentioning
confidence: 72%
“…Upon increasing the current density, the potential of the conditioned CoP NWs rises but gets stabilized quickly, indicating their outstanding mass transfer properties and mechanical robustness. 41,42 At each current density, the overpotential of the conditioned CoP NWs is significantly lower than that of the bare CF. The conditioned CoP NW electrode only needs a potential of 1.60 V (non iR -corrected) to deliver a high current density of 400 mA cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…Martindale et al reported on bi-functional iron only electrodes for full water splitting at pH 13 at a bias of ~ 2V [109] . Significant lower cell voltages of 1.65 V, 1.68 V and 1.63 V were required for overall water splitting upon CoSe [110] film, NiCo2S4 nanowires [111] and NiSe films [112] [113] and Antonietti and Shalom et. al.…”
Section: Her Properties In Acidic/alkaline Mediummentioning
confidence: 99%